(untitled) (Belügyi Szemle, 2025)
Aim: The study aims to analyse the implementation of strategic human resource management (SHRM) in European public administrations, focusing on generational challenges, workforce planning, and HRM strategies to enhance public sector attractiveness. Methodology: The research is based on a large-scale international and Hungarian study, utilizing surveys, interviews, and statistical analyses conducted among EUPAN member states and observer countries to assess HRM frameworks and generational workforce integration. Findings: The results indicate varying levels of SHRM adoption, with some countries implementing comprehensive HRM strategies while others face structural and policy challenges. Additionally, the study highlights the role of HR data-driven decision-making and the impact of generational shifts on public administration workforce planning. Value: This research provides practical recommendations for improving generational management and modernizing recruitment and retention strategies in public administration. By identifying best practices and gaps, it offers insights for policymakers and HR professionals seeking to adapt HRM frameworks to demographic changes and labour market demands.